Porcine RIG-I and MDA5 Signaling CARD Domains Exert Similar Antiviral Function Against Different Viruses - Li, Shuangjie; Shao, Qi; Zhu, Yuanyuan; Ji, Xingyu; Luo, Jia; Xu, Yulin; Liu, Xueliang; Zheng, Wanglong; Chen, Nanhua; Meurens, François; Zhu, Jianzhong (Frontiers in Microbiology, 2021)
The RIG-I like receptors (RLRs) RIG-I and MDA5 play critical roles in sensing and fighting viral infections. Although RIG-I and MDA5 have similar molecular structures, these two receptors have distinct features during activation. Further, the signaling domains of the N terminal CARD domains (CARDs) in RIG-I and MDA5 share poor similarity. Therefore, we wonder if the CARDs of RIG-I and MDA5 play similar roles in signaling and antiviral function. Here we expressed porcine RIG-I and MDA5 CARDs in 293T cells and porcine alveolar macrophages, and found that MDA5 CARDs has higher expression and stronger signaling activity than RIG-I CARDs. Nevertheless, both RIG-I and MDA5 CARDs exert comparable antiviral function against several viruses. Transcriptome analysis showed that MDA5 CARDs is more effective in regulating downstream genes. However, in the presence of virus, both RIG-I and MDA5 CARDs exhibit similar effects on downstream gene transcriptions, reflecting their antiviral function.